Rethinking Teacher Education for Inclusion: A Literature Review - Ayman Massouti (Canadian Society for Studies in Education, 2019)
This article constitutes a literature review on teacher education for inclusion. The review examines related Canadian and international research from a policy perspective and argues for reconsidering the concept of inclusion in teacher education programming to further advance the learning experiences of those who come from diverse backgrounds. The review sheds light on the existing views, beliefs, and policy practices of those involved in teacher education and attends to the processes of translating inclusion policy principles into the practices of practitioners situated in various school contexts. Further, the review examines issues of funding along with the organizational and instructional strategies that would promote teacher education for inclusion in Ontario and beyond. A concluding summary and implications for future research are offered.